Recovery of the salt marsh periwinkle (Littoraria irrorata) 9 years after the Deepwater Horizon oil spill: Size matters. (November 2020) - Deis, Donald R.; Fleeger, John W.; Johnson, David S.; Mendelssohn, Irving A.; Lin, Qianxin; Graham, Sean A.; Zengel, Scott; Hou, Aixin
Abstract: Prior studies indicated salt marsh periwinkles ( Littoraria irrorata ) were strongly impacted in heavily oiled marshes for at least 5 years following the Deepwater Horizon oil spill. Here, we detail longer-term effects and recovery over nine years. Our analysis found that neither density nor population size structure recovered at heavily oiled sites where snails were smaller and variability in size structure and density was increased. Total aboveground live plant biomass and stem density remained lower over time in heavily oiled marshes, and we speculate that the resulting more open canopy stimulated benthic microalgal production contributing to high spring periwinkle densities or that the lower stem density reduced the ability of subadults and small adults to escape predation. Our data indicate that periwinkle population recovery may take one to two decades after the oil spill at moderately oiled and heavily oiled sites, respectively. Highlights: The Deepwater Horizon oil spill oiled extensive wetland shoreline areas. Periwinkle density and shell length were quantified for 9 years after the spill. Reference, moderately and heavily oiled sites were sampled in Barataria Bay, LA. Speed of recovery of dominant salt marsh vegetation influenced periwinkle recovery. Periwinkle recovery at heavily oiled sites may take more than two decades.